2013
DOI: 10.5539/jel.v2n1p176
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technology Profiles of College Students with Learning Disabilities and Adequate and Very Poor Readers

Abstract: We interviewed 58 experts (30 in French, 28 in English) about potentially useful information and communication technologies (ICTs) for Québec college students with a learning disability (LD) and evaluated whether college students with an LD (n = 74), in fact, used these. We also compared ICT use, learning opportunities, and attitudes among three groups of students from Montreal area French and English language colleges: (1) students with an LD, and (2) students who, based on a reading comprehension test, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 5 publications
(4 reference statements)
1
12
0
Order By: Relevance
“…Moreover, over 80% of nominated professors posted these, despite the frequently voiced concern that if notes and PowerPoints are posted online, students will not attend class. However, a previous study by Fichten et al (2013) found that students self-reported that they were equally likely to attend class when course notes were and when these were not posted online. Since self-report is not actual behavior, more research is needed on how online PowerPoints and course notes influence learning and class participation.…”
mentioning
confidence: 92%
“…Moreover, over 80% of nominated professors posted these, despite the frequently voiced concern that if notes and PowerPoints are posted online, students will not attend class. However, a previous study by Fichten et al (2013) found that students self-reported that they were equally likely to attend class when course notes were and when these were not posted online. Since self-report is not actual behavior, more research is needed on how online PowerPoints and course notes influence learning and class participation.…”
mentioning
confidence: 92%
“…In addition to the apps and techniques listed in Table 3, our results highlight that what are usually considered general use apps and built-in features of mobile devices are, in fact, used as assistive aids by students with certain disabilities (e.g., Fichten et al, 2013;Fichten, Asuncion, Barile, Fossey, & De Simone, 2000). For example, the ubiquitous dictionary feature of most mobile apps can be used as assistive technology by students with literacy challenges and learning disabilities.…”
Section: General Use Features and Appsmentioning
confidence: 75%
“…For example, in one study of students with autism in higher education in Australia, a student discussed being provided with a computer to help with notetaking and to avoid handwriting legibility issues (Cai & Richdale, 2015, p. 36). However, there can be issues with the provision of ICT in these situations as students are often only permitted to use the devices for narrow purposes (Alper, 2017), despite the fact that non-specialised software and digital devices can actually be the most commonly used and most helpful assistance for students with disability (Fichten et al, 2013;Heiman, Fichten, Olenik-Shemesh, Keshet, & Jorgensen, 2017).…”
Section: Australian Students With Disability Ict Usementioning
confidence: 99%
“…In order to address some of these issues, a Quebecois study by Fichten et al (2013) involved compiling a list of ICTs that experts believed would benefit college students with learning disabilities and then asking those students which ICTs they actually used. The researchers found key discrepancies between the expert recommendations and student realities.…”
Section: Specific Issues For Students With Disability Studying Onlinementioning
confidence: 99%